(untitled) (Islamic Studies Journal for Social Transformation, 2026)
This study aims to analyze the transformation of Islamic Basic education in the era of digital globalization and examine the strategic role of educational technology in strengthening Islamic values amid the dynamics of global change. The study uses a qualitative approach with a literature review design through critical and systematic examination of scientific literature and relevant policy documents. Data analysis was conducted using interpretive content analysis techniques to identify the main themes, key concepts, and interrelationships between concepts related to the transformation of Islamic Basic education and the use of educational technology. The results show that educational technology has a strategic role in driving the transformation of Islamic Basic education through increased accessibility, quality, and inclusiveness of learning, strengthening collaborative learning, and integrating 21st-century competencies with Islamic values. The findings also reveal that the successful utilization of educational technology is largely determined by educators’ digital competencies, value orientation in learning design, and sustainable institutional policy support. This research contributes theoretically to enriching the conceptual framework of Islamic Basic education transformation in the digital era and practically provides strategic references for the development of adaptive, valuable, and contextual Islamic education policies and practices.